Ameliorative Effect of Cichoric Acid against Diabetes Associated Cognitive Decline with Emphasis on Neurobehavioral Activity, Aβ and AChE - Shukla, Sunil; Sharma, Sunil; Vasudeva, Neeru; Hooda, Tanuj (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Diabetes Mellitus (DM) is closely related to degenerative and functional abnormalities of the CNS. Studies indicate that an alteration in the CNS brought on by persistent hyperglycemia is primarily responsible for diabetes-related cognitive impairment proving a clear connection between DM and cognitive impairment. Anti-oxidants, antihyperglycemics, and insulin-sensitizing substances can lessen this diabetes-related cognitive impairment. Due to the anti-diabetic and antioxidant characteristics, Cichoric Acid (CA) might have an impact on the cognitive impairment brought on by diabetes. Aim: The goal of the current investigation was to determine if CA protects against cognitive deterioration in Streptozotocin (STZ)-induced diabetic rats. Materials and Methods: Diabetes was induced by a single i.p. injection of Streptozotocin (STZ) 60 mg per kg of body weight. After development of persistent hyperglycemia rats were treated with Cichoric Acid for both acute (14 days) and chronic (28 days) conditions followed by behavioural and biochemical analysis. Results: The levels of Aβ(1-42), serum glucose, AChE activity, and MDA levels were markedly reduced after CA treatment in comparison to the STZ infused group. In contrast, the levels of GSH were significantly elevated by CA therapy. CA therapy improved learning and memory ability in both acquisition and probe trials (Morri’s water maze tests), outperforming the STZ injection group. However, CA was found to mitigate the effects of STZ more significantly at the chronic level of treatment compared to the acute one. Conclusion: findings revealed that CA reduced cognitive impairment brought on by STZ, suggesting that CA has a lot of potential combat cognitive impairment.
Keywords: Diabetes mellitus; Cognitive dysfunction; Cichoric acid; Oxidative stress; Beta amyloid; Acetylcholinesterase